Unpacking early infant male circumcision decision-making using qualitative findings from Zimbabwe. Issue 1 (December 2017) - Mavhu, Webster; Hatzold, Karin; Ncube, Getrude; Fernando, Shamiso; Mangenah, Collin; Chatora, Kumbirai; Dhlamini, Roy; Mugurungi, Owen; Ticklay, Ismail; Cowan, Frances
Abstract Background Early infant male circumcision (EIMC) has been identified as a key HIV prevention intervention. Exploring the decision-making process for adoption of EIMC for HIV prevention among parents and other key stakeholders is critical for designing effective demand creation interventions to maximize uptake, roll out and impact in preventing HIV. This paper describes key players, decisions and actions involved in the EIMC decision-making process. Methods Two complementary qualitative studies exploredhypothetical andactual acceptability of EIMC in Zimbabwe. The first study (conducted 2010) exploredhypothetical acceptability of EIMC among parents and wider family through focus group discussions (FGDs, n = 24). The follow-up study (conducted 2013) exploredactual acceptability of EIMC among parents through twelve in-depth interviews (IDIs), four FGDs and short telephone interviews with additional parents (n = 95). Short statements from the telephone interviews were handwritten. FGDs and IDIs were audio-recorded, transcribed and translated into English. All data were thematically coded. Results Study findings suggested that EIMC decision-making involved a discussion between the infant's parents. Male and female participants of all age groups acknowledged that the father had the final say. However, discussions around EIMC uptake suggested that the infant's mother could sometimes covertly influence the father's decision in the direction she favoured. Discussions also suggested that fathers who had undergone voluntary medical male circumcision were more likely to adopt EIMC for their sons, compared to their uncircumcised counterparts. Mothers-in-law/grandparents were reported to have considerable influence. Based on study findings, we describe key EIMC decision makers and attempt to illustrate alternative outcomes of their key actions and decisions around EIMC within the Zimbabwean context. Conclusions These complementary studies identified critical players, decisions and actions involved in the EIMC decision-making process. Findings on who influences decisions regarding EIMC in the Zimbabwean context highlighted the need for EIMC demand generation interventions to target fathers, mothers, grandmothers, other family members and the wider community.